AUTHORITY AND INTERACTION OF ACTORS OF EXECUTIVE AUTHORITY OF MOSCOW CITY AND BODIES OF LOCAL SELF-GOVERNMENT IN THE FIELD OF RATIONAL WASTE MANAGEMENT - N. Musinova (Вестник университета)
The problem of organization of management in a field of rational recycling of solid municipal waste (LFW) in Moscow is discussed in the article. The only way towards a waste-free technology is a separate collection of LFW by the population. The key link in the organization of this process could be the bodies of local self-government, but their role in this sphere has not yet been defined. Clarification of the powers of the executive branch is also required. In this regard, the regulation of inter-level interaction between Moscow executive agencies and local self-government bodies of intracity municipalities should become a tool for solving the organizational problems.